(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article explores effective ways of developing linguistic competence in students in the process of teaching foreign languages. Linguistic competence, which includes knowledge of grammar, vocabulary, phonology, and syntax, plays a crucial role in language acquisition. The study aims to analyze modern teaching methods and their impact on students’ linguistic development. Both theoretical and practical approaches are considered, including communicative language teaching, task-based learning, and the integration of digital technologies. The findings show that interactive and student-centered approaches significantly improve linguistic competence. The article concludes with recommendations for teachers to enhance language instruction.